2008
DOI: 10.1111/j.1365-2702.2006.01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to clean intermittent self‐catheterization procedures: determinants explored

Abstract: Issues of knowledge, fears, motivation and potential psychological impact of performing CISC should be addressed prior to deciding on CISC and instructing patients. Follow-up care should be improved to include re-evaluations of skills, discussing adherence, integrating CISC in daily activities and general coping issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 18 publications
4
70
0
1
Order By: Relevance
“…There are few studies aiming to determine the CISC adherence rate and the variables related to it. Van Achterberg et al (10) performed a study with 20 patients to determine the important factors in patient's long-term adherence. They were not able to find a significant variable to correlate with patient's adherence and concluded that it would be important to perform a more specific study to evaluate the adherence rate to CISC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies aiming to determine the CISC adherence rate and the variables related to it. Van Achterberg et al (10) performed a study with 20 patients to determine the important factors in patient's long-term adherence. They were not able to find a significant variable to correlate with patient's adherence and concluded that it would be important to perform a more specific study to evaluate the adherence rate to CISC.…”
Section: Discussionmentioning
confidence: 99%
“…The bladder diary was also used to evaluate adherence to procedure. Patients were considered adherent to the program if they were performing at least 80% of the initial recommendation (10,12,13). The adherence rate was evaluated by patient´s report in the 3 days bladder dairy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In older patients, physical and mental impairments can preclude the use of CIC, leaving suprapubic catheterization as the only treatment option. 7 Latissimus dorsi detrusor myoplasty was intended for a distinct group of patients suffering from an acontractile bladder and treatment-related adverse effects. 8 Certainly, any surgical procedure restoring lower urinary tract function must prove its uro dynamic safety over the long term.…”
Section: Georgios Gakis Milomir Ninkovic and Arnulf Stenzlmentioning
confidence: 99%
“…Good adherence to intermittent catheterization is important to realize the benefits. A nontraumatizing catheterization technique with adequate frequency and complete emptying should be strictly adhered to in order to reduce the likelihood of complications [1,2] .Studies have shown that initial adherence to catheterization can be influenced by factors including the perception of increased sickness on starting catheterization whereas long-term adherence can be influenced by factors such as the time needed to perform catheterization, fear of damaging the urinary tract, and the patient's image of self and self-efficacy [3,4] . The user's need for privacy and discretion to avoid embarrassment [4,5] can be supported by catheterization equipment that is less visu-…”
mentioning
confidence: 99%